Den Norden lesen: Erinnerungen, Wahrnehmungen und Bedeutungen im interdisziplinären Dialog - Mittner, Lilli; Wagner, Gabriela (Nordlit, 2020)
Our contribution is based on the method of dramatic assemblage (Klok and Haselmann 2019). Encountering two autoethnographic literary sources – The Doctor’s Family in the Far North (Gjems Selmer 1905) and A Woman in the Polar Night (Ritter 1938) we move between different temporal and disciplinary thinking practices. In our respective roles as cultural scientist and biologist we enter a research dialogue about experiences, representations, and meanings of ‘the north’. Our focus is on modes in which the north is expressed in both memory-based literary memoirs and current academic perceptions. The dramatic assemblage shows that the north gains concrete meaning in the multimodal interplay of rhythms, sounds, light, temperatures, smells, and colours of landscapes, people, animals, plants, and the relations between these. By approaching the north through an interdisciplinary and co-creative approach, newly gained knowledge becomes both relevant and accessible to a variety of academic fields.